Preparation of pH‐responsive metal chelate affinity polymer for adsorption and desorption of insulin. Issue 7 (21st December 2016) - Ding, Zhaoyang; Kang, Lin; Liu, Jifu; Zhang, Xuanjun; Cao, Xuejun
Abstract: BACKGROUND: Insulin is a medicine for diabetes mellitus that is used worldwide. This study focuses on the preparation of a pH‐responsive metal chelated affinity polymer and the adsorption of insulin by this polymer. RESULTS: The pH‐responsive polymer was synthesized and zinc ions were attached to the polymers as the affinity polymer PMMDN ‐Zn 2+, which can adsorb insulin. The molecular weight, isoelectric point (pI) which is the pH at which the net charge on the polymer is zero, and other characteristics of the polymers were determined. Circular dichroism spectroscopy was performed to analyze the interaction between the metal ions and insulin. The optimum adsorption conditions, including the time, pH, salt concentrations and insulin concentrations were investigated. The pI of the polymer was 3.41 and the recovery of the polymer was 97.5%. The maximum adsorption capacity of PMMDN ‐Zn 2+ towards insulin was 162.3 mg insulin g −1 polymer. CONCLUSION: This results suggest that the affinity polymer PMMDN ‐Zn 2+ has potential for application on a large scale due to its high recovery rates and high adsorption capacity. © 2016 Society of Chemical Industry